Single-Gene Deletion Mutants of Escherichia coli with Altered Sensitivity to Bicyclomycin, an Inhibitor of Transcription Termination Factor Rho - Tran, Lillian (American Society for Microbiology, 2011)
We have screened the entire KEIO collection of 3,985 single-gene knockouts in Escherichia coli for increased susceptibility or resistance to the antibiotic bicyclomycin (BCM), a potent inhibitor of the transcription termination factor Rho. We also compared the results to those of a recent study we conducted with a large set of antibiotics (A. Liu et al., Antimicrob. Agents Chemother. 54:1393-1403, 2010). We find that deletions of many different types of genes increase sensitivity to BCM. Some of these are involved in multidrug sensitivity/resistance, whereas others are specific for BCM. Mutations in a number of DNA recombination and repair genes increase BCM sensitivity, indicating that DNA damage leading to single- and double-strand breaks is a downstream effect of Rho inhibition. MDS42, which is deleted for all cryptic prophages and insertion elements (G. Posfai et al., Science 312:1044-1046, 2006), or W3102 deleted for the rac prophage-encoded kil gene, are partially resistant to BCM (C. J. Cardinale et al., Science 230:935-938, 2008). Deletion of cryptic prophages also overcomes the increased BCM sensitivity in some but not all mutants examined here. Deletion of the hns gene renders the cell more sensitive to BCM even in the Δkil or MDS42 background. This suggests that BCM activates additional modes of cell death independent of Kil and that these could provide a target to potentiate BCM killing.